2020
DOI: 10.34172/jrhs.2020.31
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of E-Learning Program in Preventing WP Smoking in Adolescent Females in West of Iran by Applying Prototype-Willingness Model: A Randomized Controlled Trial

Abstract: Background: Given the increasing trend of Water pipe (WP) smoking in adolescent females, it is necessary to use effective educational strategies in preventing WP smoking in developing countries. We aimed to determine effectiveness of e-learning program in preventing WP smoking in adolescent females west of Iran using prototype-willingness model. Study Design: A randomized controlled trial. Methods: This study was performed on 221 adolescent females in Kermanshah City, Iran during 2019-2020. Multistage random s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 32 publications
3
16
0
Order By: Relevance
“…Hence, one of the reasons for adjusting the perceived barrier score of the experimental group in this study can be the increase in self-efficacy, which matches the results of Solhi and Abolfathi (36), Giti and Shojaizadeh (37), and Rakhshani et al (28), while not being in line with the results of Panahi et al (13) and Lee et al (15). In the present study, the mean score of cues to action in the experimental group significantly increased after education, and a significant difference was found between the two groups in this respect, which is consistent with the results of Bashirian et al (39) Based on the results of this study the mean selfefficacy score of the intervention group demonstrated a considerable increase after training, and there was a significant difference between the two groups in terms of this variable. Self-efficacy is defined as a person's belief and confidence in their abilities to successfully perform a behavior and is a vital and influential construct emphasized in educational theories (39).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Hence, one of the reasons for adjusting the perceived barrier score of the experimental group in this study can be the increase in self-efficacy, which matches the results of Solhi and Abolfathi (36), Giti and Shojaizadeh (37), and Rakhshani et al (28), while not being in line with the results of Panahi et al (13) and Lee et al (15). In the present study, the mean score of cues to action in the experimental group significantly increased after education, and a significant difference was found between the two groups in this respect, which is consistent with the results of Bashirian et al (39) Based on the results of this study the mean selfefficacy score of the intervention group demonstrated a considerable increase after training, and there was a significant difference between the two groups in terms of this variable. Self-efficacy is defined as a person's belief and confidence in their abilities to successfully perform a behavior and is a vital and influential construct emphasized in educational theories (39).…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, the mean score of cues to action in the experimental group significantly increased after education, and a significant difference was found between the two groups in this respect, which is consistent with the results of Bashirian et al (39) Based on the results of this study the mean selfefficacy score of the intervention group demonstrated a considerable increase after training, and there was a significant difference between the two groups in terms of this variable. Self-efficacy is defined as a person's belief and confidence in their abilities to successfully perform a behavior and is a vital and influential construct emphasized in educational theories (39). Accordingly, in designing educational programs, the special and practical role of this construct should be considered regarding habitual behaviors such as smoking behavior or smoking prevention.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In this study, the results indicate that having a friend who smokes WPs increases the probability of WP smoking, similar to the results of a study. [ 13 25 26 ]…”
Section: Discussionmentioning
confidence: 99%
“…This theory holds that adolescents derive their beliefs about high-risk behaviors from role models, especially close friends and parents. [ 26 36 ]…”
Section: Discussionmentioning
confidence: 99%